Pengaruh Reliabilitas Dan Empati Terhadap Kepuasan Pelanggan Eksternal (Pasien) Di RSUD Kota Padangpanjang: Indonesia - Ulima Harma (Prodi Ilmu Administrasi Negara, 2018)
The aims of this research is to know reliability and emphaty at RSUD Padangpanjang city. The purpose of this research was to know influence reliability and emphaty on patient satisfaction at RSUD Padangpanjang city. This research used aquantitative method with three exogenous variables; reliability(X1) and emphaty (X2), besides one endogenous variable, was on patients satisfaction(Y). The participants of this research were about 53.363 who were all patients at RSUD Padangpanjang city. This research used Slovin formula, with5% standard error, so the participants in this research were 397. The sample in this research was collected in ways: cluster or are a random sampling. This analysis used multiple linear regression. The result of research is findings of hipotesys model, can make a new model of service quality at RSUD Padangpanjang city can be improve satisfaction of patients in healthcare. Findings of research is: 1) there is influence of reliability on patients satisfaction is 0,01346 with sign.0,000, 2)there is influence of emphaty on patients satisfaction is 0,03648 with sign.0,000, 3) there is influence of reliability and emphaty on patients satisfaction is 0,00097 with sign. 0,000.